2009
DOI: 10.1017/s0031182009006374
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Culicoides species composition and abundance in avian nests

Abstract: Mechanisms affecting patterns of vector distribution among host individuals may influence the population and evolutionary dynamics of vectors, hosts and the parasites transmitted. We studied the role of different factors affecting the species composition and abundance of Culicoides found in nests of the blue tit (Cyanistes caeruleus). We identified 1531 females and 2 males of 7 different Culicoides species in nests, with C. simulator being the most abundant species, followed by C. kibunensis, C. festivipennis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 60 publications
9
44
0
Order By: Relevance
“…Most species of the genus Culicoides are known to be either mammalophilic (Hair and Turner, 1968;Foxi and Delrio, 2010;Garros et al, 2011;Calvo et al, 2012) or ornithophilic (Bennett, 1960;Hair and Turner, 1968;Garvin and Greiner, 2003;Mullens et al, 2006; Martinez-de la Puente et al, 2009;Votypka et al, 2009;Foxi and Delrio, 2010;Cerny et al, 2011), although some feed on reptiles or frogs. In a previous study using animal-baited traps, horses were found to be the most attractive hosts for the three main Palaearctic Culicoides species, including C. obsoletus (Viennet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most species of the genus Culicoides are known to be either mammalophilic (Hair and Turner, 1968;Foxi and Delrio, 2010;Garros et al, 2011;Calvo et al, 2012) or ornithophilic (Bennett, 1960;Hair and Turner, 1968;Garvin and Greiner, 2003;Mullens et al, 2006; Martinez-de la Puente et al, 2009;Votypka et al, 2009;Foxi and Delrio, 2010;Cerny et al, 2011), although some feed on reptiles or frogs. In a previous study using animal-baited traps, horses were found to be the most attractive hosts for the three main Palaearctic Culicoides species, including C. obsoletus (Viennet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, some important characteristics of nests location such as the distance to water sources do not affect the abundance of biting midges in blue tit nests (Tomás et al, 2008a). It is clear that host related factors, including brood size and hatching date, as well as weather conditions during the insect sampling period are of major importance to influence the abundance of biting flies in avian nests (Martínez-de la Puente et al, 2009aPuente et al, , 2009b. Furthermore, our results suggest that nest temperature did not affect significantly the presence/absence of black flies in avian nests.…”
Section: Discussionmentioning
confidence: 58%
“…The Spanish National Meteorological Institute provided daily maximum and minimum temperature data from the closest meteorological station located in Segovia, approximately 9 km from the study area. In previous studies, data from this meteorological station have been used to find clear effects of weather on several factors related to avian biology and birdehaematophagous insect interactions carried out in the same area (Sanz et al, 2003;Lobato et al, 2006;Martínez-de la Puente et al, 2009b). Environmental temperature was then estimated by calculating the averages of the maximum and minimum temperatures respectively for each insect sampling period.…”
Section: Rearing Conditions In the Nests And Weather Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations